PENGARUH KEPEMILIKAN MANAJERIAL, DEBT COVENANT, DAN GROWTH OPPORTUNITIES PADA PERUSAHAAN GO PUBLIC TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris Pada PerusahaanManufaktur Yang TerdaftarDi Bei Periode 2011-2016) - Novita, Elva Chelia; Kamaliah, Kamaliah; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Purpose This Research is to Analyze The Effect Of Managerial Ownership, Debt Covenant And Growth Opportunities To Application Conservatism On Accounting On The Manufacture Company Listed Go Public On The BEI. The population in this study are companies listed on the BEI in 2011 - 2016. The sample studied consisted of 83 samples of Manufacture companies from 2011-2016. The analysis technique used to perform hypothesis testing is purposive sampling.The results show that the Managerial Ownership And growth Opportunities Has Effect on Accounting Conservatism, while Debt Covenant has no effect on the Accounting Conservatism. The Managerial Ownership shows a significance value of 0.000. The Debt Covenant shows a significance value of 0.0289. The Growth Opportunities shows a significance value of 0.017.Keyword : Accounting Conservatism, Managerial Ownership, Debt Covenant, And Growth Opportunities.